The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/s23042152
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Analysis on Electrocardiograms, Seismocardiograms and Gyrocardiograms of Healthy Volunteers and Patients with Valvular Heart Diseases

Abstract: Heart rate variability (HRV) is the physiological variation in the intervals between consecutive heartbeats that reflects the activity of the autonomic nervous system. This parameter is traditionally evaluated based on electrocardiograms (ECG signals). Seismocardiography (SCG) and/or gyrocardiography (GCG) are used to monitor cardiac mechanical activity; therefore, they may be used in HRV analysis and the evaluation of valvular heart diseases (VHDs) simultaneously. The purpose of this study was to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…This study demonstrated that acceptable HRV indices can be computed from NCC local maxima provided by the ECG-free heartbeat detection method based on template matching, which overcomes potential issues in localizing SCG/GCG fiducial points. It is also worth underlining that only [88][89][90] analyzed signals from pathological subjects, while all other studies focused on small cohorts of healthy subjects. In addition, many of these studies do not report the number of inter-beat intervals considered for HRV analysis, which impacts the reliability of the statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that acceptable HRV indices can be computed from NCC local maxima provided by the ECG-free heartbeat detection method based on template matching, which overcomes potential issues in localizing SCG/GCG fiducial points. It is also worth underlining that only [88][89][90] analyzed signals from pathological subjects, while all other studies focused on small cohorts of healthy subjects. In addition, many of these studies do not report the number of inter-beat intervals considered for HRV analysis, which impacts the reliability of the statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect makes heartbeat detection a much more complex task. Few studies by Sieci ński et al investigated the feasibility of HRV analysis on cardio-mechanical signals of pathological subjects [88][89][90]. Specifically, HRV indices obtained from the SCG and/or GCG signals of 30 healthy volunteers and 30 patients with valvular heart diseases (VHDs) were compared with those computed from reference ECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these waves carries information about heart wellness [3,4]. For instance, although it is not possible to fully analyze heart wellness by analyzing only the R waves, the R-peaks and, more precisely, the intervals between R-peaks and their variability, called the Heart Rate Variability (HRV), carry enough information to diagnose several heart diseases, including arrhythmia [5] and valvular heart diseases [6].…”
Section: A Ecg Signal Backgroundmentioning
confidence: 99%
“…6 presents the implementation of the R-peak detector. This is the main component of the system, as R-peaks carry enough information to diagnose several heart diseases, such as arrhythmia [5] and valvular heart diseases [6].…”
Section: R-peak Detector Circuitmentioning
confidence: 99%
“…The existing body of literature has exploited HR and HRV in the studies of cardiovascular health and disease (Stein et al 2007, Haensel et al 2008, Thayer et al 2010, Hillebrand et al 2013, Soares-Miranda et al 2014, physical fitness (Plews et al 2013, Mongin et al 2022, mental health (Kemp and Quintana 2013, Quintana and Heathers 2014, Beauchaine and Thayer 2015, Pham et al 2021, and cognitive impairments (Luft et al 2009, Quintana et al 2012, Forte et al 2019. The use of HR and HRV in research and practice is expected to rapidly expand given the remarkable advances in wearable sensing technology to conveniently measure the physiological signals bearing HR and HRV, including electrocardiogram (ECG) (Sieciński et al 2020, Pham et al 2021, Parreira et al 2023, photoplethysmogram (PPG) (Lu et al 2008, Uçar et al 2018, and seismocardiogram (SCG) (Hurnanen et al 2017, Sieciński et al 2020 and ballistocardiogram (BCG) (Shin et al 2011, Brüser et al 2013 to list a few.…”
Section: Introductionmentioning
confidence: 99%